ETHNOPHARMACY SUKU ANAK DALAM OF BUNGKU VILLAGE, BAJUBANG DISTRICT, BATANGHARI REGENCY, JAMBI PROVINCE IN 2021 - Puspa Dwi pratiwi (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
Suku Anak Dalam (SAD), the one of ethnics in Indonesia precisely on Jambi Province still use various types of plants and animals part as medical substance. Traditional medicine among local ethnics has differences of each other. In addition, the depletion of forests as a source of life and modern culture make traditional medicine been forgotten. The aim of this study was determine the souce of natural products used by SAD for medical purposes. It was a descriptive study using purposive sampling and snow ball sampling to get as much data as possible about medicinal plants or animals used by Suku Anak Dalam, Bungku Village. The results showed that there were 17 plats and 4 animals used by SAD for medicine. The disease are often experienced by Suku Anak dalam are stomachache, dyspepsia, kidney desease, dengue, hyperlipidemia, vulnus, toothache, and ascariasis. The part of natural product frequently used include root, stem, leaves, and sap, which were commonly processed by boiling, mashing, eating, searing, sticking, and burning. Based on the results that has been done that were 17 plants and 4 animals from different genus and family used as traditional medicine with different part and processed.